Multiple evidences reveal new species and a new record of smelly Gymnopus (Agaricales, Omphalotaceae) from China - Hu, Jia-Jun; Song, Li-Ru; Tuo, Yong-Lan; Zhao, Gui-Ping; Yue, Lei; Zhang, Bo; Li, Yu (Frontiers in Microbiology, 2022)
Gymnopus sect. Impudicae is a poorly studied group around the world. However, it is well known for its pungent smell—a total of five species from China belonging to sect. Impudicae were recorded, and included four species new to science—Gymnopus epiphyllus, Gymnopus cystidiosus, Gymnopus subdensilamellatus, and Gymnopus subpolyphyllus—which were delimited and proposed based on morphological and molecular evidence and one new record from Henan, Jiangxi, and Gansu Province, China—Gymnopus densilamellatus. Detailed descriptions and illustrations were presented as well as comparisons to similar species. The phylogenetic analysis inferred from the ITS and nLSU data set supported the Gymnopus, defined by Oliveira et al., as a monophyletic genus and the novel species as separate lineages within. A key to all species described in this study is also provided.